Floral Cues of Non-host Plants Attract Oligolectic Chelostoma rapunculi Bees - Burger, Hannah; Joos, Nadine; Ayasse, Manfred (Frontiers in Ecology and Evolution, 2021)
Oligolectic bees are highly dependent on the availability of the host plants to which they are specialized. Nevertheless, females of Chelostoma rapunculi have recently been monitored occasionally to visit Malva moschata and Geranium sanguineum flowers, in addition to their well-known Campanula spp. hosts. The questions therefore arise which floral cues promote visits to non-host plants. As host-specific floral cues are key attractants for oligolectic bees, we have studied the attractiveness of olfactory and visual cues of the established host Campanula trachelium in comparison to the non-host plants G. sanguineum and M. moschata in behavioral experiments. Chemical and electrophysiological analyses of the floral scent and spectral measurements of floral colors were used to compare and contrast host and non-host plants. The behavioral experiments showed that foraging-naïve bees, in particular, were attracted by olfactory cues of the non-host plants, and that they did not favor the Campanula host scent in choice experiments. Many electrophysiologically active floral volatiles were present in common in the studied plants, although each species produced an individual scent profile. Spiroacetals, the key components that enable C. rapunculi to recognize Campanula hosts, were detected in trace amounts in Geranium but could not be proved to occur in Malva. The visual floral cues of all species were particularly attractive for foraging-experienced bees. The high attractiveness of G. sanguineum and M. moschata flowers to C. rapunculi bees and the floral traits that are similar to the Campanula host plants can be a first step to the beginning of a host expansion or change which, however, rarely occurs in oligolectic bees.